ANALISA HARMONISA PEMBANGKIT LISTRIK TENAGA SURYA (PLTS) OFF - GRID 290 Wp DENGAN KOMBINASI BEBAN LINIER DAN NON LINIER DI GEDUNG FAKULTAS TEKNIK UKI - JAKARTA MENGGUNAKAN MATLAB SIMULINK - Openg, Elisabeth Faustina Ene; Widodo, Bambang; Purba, Robinson (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2024)
This paper presents the results of research on a 290 Wp (Watt-peak) Off-Grid Solar Power Plant (PLTS) at the Faculty of Engineering Building, Universitas Kristen Indonesia - Jakarta, aiming to investigate current harmonics on the load side and reduce the Total Harmonic Distortion (THDi) value using a single-tuned LC passive filter. Based on the measured current per order, calculations were conducted, revealing that the THDi on the load side (LED) amounted to 16,42%. The dominant harmonic currents were the 3rd order with a THDi of 5,7% and the 10th order with a THDi of 15,3%. According to the simulation results using MATLAB Simulink, the single-tuned LC passive filter was capable of reducing the THDi level on the LED from 16,42% to 1,81%.